2010
DOI: 10.1109/tcapt.2009.2022949
|View full text |Cite
|
Sign up to set email alerts
|

Capacitive Pressure Sensor With Very Large Dynamic Range

Abstract: A new capacitive pressure sensor with very large dynamic range is introduced. The sensor is based on a new technique for substantially changing the surface area of the electrodes, rather than the inter-electrode spacing as commonly done at the present. The prototype device has demonstrated a change in capacitance of approximately 2500 pF over a pressure range of 10 kPa.Index Terms-Capacitive pressure sensor, pressure sensor, sensor dynamic range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 11 publications
0
29
0
Order By: Relevance
“…We shall therefore replace in (7) by , where is the peak value of the acceleration. Equation (7) then yields (8) From (3) and (8), we conclude that (9) If the sensor is subjected to a frequency , the above expression will reduce to (10) where was determined to be approximately equal to 0.8 for the present sensor (see Section III-B). For a capacitance in the pico-Farad range, it can be seen that the detectable acceleration will be on the order of m/s , or .…”
Section: B Sensing Of Vibrationsmentioning
confidence: 93%
See 1 more Smart Citation
“…We shall therefore replace in (7) by , where is the peak value of the acceleration. Equation (7) then yields (8) From (3) and (8), we conclude that (9) If the sensor is subjected to a frequency , the above expression will reduce to (10) where was determined to be approximately equal to 0.8 for the present sensor (see Section III-B). For a capacitance in the pico-Farad range, it can be seen that the detectable acceleration will be on the order of m/s , or .…”
Section: B Sensing Of Vibrationsmentioning
confidence: 93%
“…In addition, a highly sensitive pressure sensor (a sensor with a capability to detect pressures of less than one Pascal) will be very useful for a new class of biological and molecular sensing applications [7], [8]. It has recently been demonstrated that sensors based on variable capacitance can offer the highest sensitivity among all known types of pressure/vibration sensing mechanisms [9]- [13]. However, capacitive pressure/vibration sensors still cannot offer the ultrahigh sensitivity that is needed for demanding applications such as earthquake prediction and the detection of very small pressures in biological processes.…”
Section: Introductionmentioning
confidence: 99%
“…But in the industrial security zone, against bad conditions, micro pressure leak in confined Spaces and test requirements for pipeline microflow have not been satisfied, need small size, high anti-interference, high sensitivity, micropressure sensor products with wide range and not lose the precision. In recent years, the development direction of micropressure sensor is starting to shift to new materials, new mechanism and new structure, the process is being developed from silicon micropressure sensor [3,4] to optical micropressure sensor.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, a constant pressure is fed to one side of the diaphragm using a pressure chamber while the other side encounters the variable pressure to be measured. The diaphragm deformation can be measured using different mechanisms, including optical [6], capacitive [7], piezoresistive [8] and resonant frequency shift [9], [10] methods. Among such, resonant pressure sensors have the advantages of simplifying readout system by providing an output frequency that can be directly fed into a computer (no need for A/D conversion), long term stability and higher resolution.…”
Section: Introductionmentioning
confidence: 99%